Vaccination Gap, Vaccination Fraud and Inefficient Testing - Hanno Beck; Aloys Prinz; Elmar Wolfstetter (Intereconomics)
Abstract A number of shortcomings in Germany’s efforts to contain the spread of the coronavirus, including fraudulent testing, vaccination fraud and insufficient testing capacity have been identified and need to be remedied before another wave or worse, another pandemic. This paper examines the failures of the deterrence instruments and proposes solutions to address them.